Online monitoring method of hydrate agglomeration in natural gas pipelines based on acoustic active excitation. (October 2016) - Qu, Zhigang; Wang, Huayang; An, Yang; Yue, Huanhuan; Li, Jian; Zhang, Yu; Wang, Yanfen; Yue, Tingting; Zhou, Weibin
Highlights: The method is able to detect and locate hydrate agglomeration in a pipeline online. Modeling work has been presented for hydrate detection and localization. Experiments have shown good localization accuracy for hydrate. Abstract: Natural gas hydrate, which forms and agglomerates under the condition of low temperature and high pressure, can easily affect production or even lead to serious accidents. In order to prevent hydrate agglomeration in a pipeline, the industries generally add seriously excess inhibitor with experience, which causes serious environmental pollution and huge costs. However, due to the uncontrollable production and environmental conditions, hydrate plugging in a pipeline still occurs. According to the issues above, the method, for hydrate agglomeration online monitoring in a natural gas pipeline based on acoustic active excitation, has been presented in this paper. The method is to monitor and locate the hydrate agglomeration in a pipeline in order to take measures in time. Both the modeling and the experimental results show that the method can monitor and locate the hydrate agglomeration online at different locations with good accuracy.